Ideal vs real perceived influence of tagalog romance novels on the relationship expectations of female college students in Iloilo City. - Escoro, Myra Integro
This study is entitled Ideal vs. Real: Perceived Influence of Tagalog Romance Novels on the Relationship Expectations of Female College Students in Iloilo City. Using the Neo-Behaviorism Theory of Edward Tolman and his Stimulus-Organism-Response Model, the study aimed to determine the level of perceived influence of reading Tagalog romance novels on the relationship expectations of female college students in Iloilo City. This is determined by the level of the respondents' exposure to Tagalog romance novels, comparison of the similarities of the characteristics they desire in the protagonists of the said novels and the actual characterisitcs they observe in the men of their current relationship status, and their expectations in their current relationship status. A total of 100 respondents were surveyed. After the data were gathered and analyzed, the researchers found that the respondents have a low level of exposure to Tagalog romance novels. Majority of the respondents considered the traits: hardworking/responsible, gentleman/protective, thoughtful/sweet/romantic/full of surprises, skillful in many things/talented, and friendly/sociable as the most attractive traits in the male protagonists of the said novels, at the same time, these are the most common characteristics among the men in the respondents' current relationship status. The most attractive characteristic in the male protagonists is Hardworking/Responsible while Friendly/ Sociable is the most common among the men in the current relationship status. Majority of female college students who read Tagalog romance novels have moderate level of expectations when it comes to their relationship status. Moreover, most of the female college students who read Tagalog romance novels perceive that reading such novels have a moderate level of influence on their relationship expectations.